Illustrated key to the species in the genus Sephina (Hemiptera: Heteroptera: Coreidae: Coreinae: Spartocerini), with descriptions of three new species and new distributional records - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2021)
Three new species of Sephina Amyot and Serville 1843, are described: S. crassa from Ecuador, S. effrena from Colombia and S. ornata from Panama. A key to the 27 known species and photographs of the dorsal habitus are included. Also included are photographs of the male genital capsule of S. vinula Stål 1862, and parameres of S. indierae Wolcott 1924 and S. vinula. New distributional records for S. dorsalis (White 1842), S. esquivelae Brailovsky & Sánchez 1983, S. faceta Brailovsky 2001, S. formosa (Dallas 1852), S. geniculata Distant 1881, S. limbata Stål 1862, S. nigripes Schmidt 1907, S. pagella Brailovsky & Sánchez 1983, S. pubera (Erichson 1848), S. pustulata (Fabricius 1803), S. rogersi Distant 1881, S. subulata Brailovsky & Sánchez 1983, and S. vinula are included. Sephina excellens Schmidt, 1907 is synonymized under S. pubera (Erichson 1848). The synonymy of Sephina grayi Van Duzee, 1909 under S. gundlachi (Guérin-Méneville 1857) is here corroborated.